A newly synthesized hydrazone derivative as a fluorescent enhancement chemosensor for sensitive detection of Cd2+ Ions - Basaran, Beyza; Aksuner, Nur; Henden, Emur; Yilmaz, Ibrahim; Cukurovali, Alaaddin (American Scientific Publishers, 2016)
A highly sensitive chemical sensor procedure for Cd2+ based on fluorescent measurements was accomplished by using of Chloroacetic acid N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N-pyridin-2-ylmethylene-hydrazide ligand immobilized in PVC films. This membrane gives a linear response in the concentration range between 1.0×10-10 and 1.0×10-5 M with a limit of detection of 7.2×10-11 M at pH 5.5. The membrane can be used over a period of four months with good reproducibility. It is selective over a number of anions and cations and can be regenerated with 0.1 M EDTA solution. The proposed sensor was applied to the determination of cadmium in real water samples. The sensor provides a low cost and fast method for the determination of Cd2+. © 2016 American Scientific Publishers.
Keywords: Cadmium(II); Fluorescence Enhancement; Fluorescence Spectroscopy; Hydrazone Derivative.; Optical Sensor; PVC Matrix